Endovascular Thrombectomy for Treatment of Acute Ischemic Stroke During Pregnancy and the Early Postpartum Period. Issue 12 (20th September 2021) - Dicpinigaitis, Alis J.; Sursal, Tolga; Morse, Catherine A.; Briskin, Camille; Dakay, Katarina; Kurian, Christeena; Kaur, Gurmeen; Sahni, Ramandeep; Bowers, Christian; Gandhi, Chirag D.; Mayer, Stephan A.; Al-Mufti, Fawaz
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Acute ischemic stroke (AIS) is a rare occurrence during pregnancy and the postpartum period. Existing literature evaluating endovascular mechanical thrombectomy (MT) for this patient population is limited. Methods: The National Inpatient Sample was queried from 2012 to 2018 to identify and characterize pregnant and postpartum patients (up to 6 weeks following childbirth) with AIS treated with MT. Complications and outcomes were compared with nonpregnant female patients treated with MT and to other pregnant and postpartum patients managed medically. Complex samples regression models and propensity score matching were implemented to assess adjusted associations and to address confounding by indication, respectively. Results: Among 4590 pregnant and postpartum patients with AIS, 180 (3.9%) were treated with MT, and rates of utilization increased following the MT clinical trial era (2015–2018; 1.9% versus 5.3%, P =0.011). Compared with nonpregnant patients with AIS treated with MT, they experienced lower rates of intracranial hemorrhage (11% versus 24%, P =0.069) and poor functional outcome (50% versus 72%, P =0.003) at discharge. Pregnant/postpartum status was independently associated with a lower likelihood of development of intracranial hemorrhage (adjusted odds ratio, 0.26 [95% CI, 0.09–0.70]; P =0.008) following multivariable analysis adjusting for age, illness severity, and stroke severity. Following propensity score matching, pregnant and postpartum patients treated with MT and those medically managed differed in frequency of venous thromboembolism (17% versus 0%, P =0.001) and complications related to pregnancy (44% versus 64%, P =0.034), but not in functional outcome at discharge or hospital length of stay. Pregnant and postpartum women treated with MT did not experience mortality or miscarriage during hospitalization. Conclusions: This large-scale analysis utilizing national claims data suggests that MT is a safe and efficacious therapy for AIS during pregnancy and the postpartum period. In the absence of prospective clinical trials, population-based cross-sectional analyses such as the present study provide valuable clinical insight.